(untitled) (Bangladesh Journal of Medicine, 2018)
Background: Diabetes mellitus is one of the most widespread endocrine disorder in female and its complications are increasing all over the world, leading to life threatening medical problems like cardiovascular diseases, stroke and end stage renal diseases. An association between hypertension and diabetes mellitus has been identified. Objectives: The study was carried out to observe the association of hypertension with diabetes mellitus in adult female subjects. Methods : This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, during the period of January 2011 to December 2011. A total number of one hundred female subjects were selected with age ranging from30 to50 years. Among them 50 diabetic female subjects were included from out-patient department of Endocrinology, Dhaka Medical College Hospital, Dhaka as study group(B) and 50 apparently healthy female were taken as control group(A) for comparison. Fasting serum insulin level was measured by ELISA method in the Department of Laboratory of National Institute of ENT, Dhaka and fasting blood glucose was estimated by glucose oxidase method in Department of Dhaka Medical College in both groups. Systolic blood pressure and diastolic blood pressure of all participants were recorded by standard method. Data was analyzed by Unpaired Student’s- test and Pearson’s correlation co-efficient (r) test as applicable. Results: The value of fasting serum insulin level was significantly higher in diabetic subjects than those of non-diabetic subjects. Fasting blood glucose level was significantly higher diabetic patient in comparison to those of non-diabetic subjects. In diabetic subjects fasting serum insulin and fasting blood glucose levels were higher and showed positive correlation with systolic and diastolic blood pressure. Conclusion: Present study revealed that systolic and diastolic blood pressure has positive relationship with fasting serum insulin and fasting blood glucose levels. Bangladesh J Medicine Jan 2018; 29(1) : 7-12